2021
DOI: 10.1038/s41598-021-01497-8
|View full text |Cite
|
Sign up to set email alerts
|

Hatching phenology is lagging behind an advancing snowmelt pattern in a high-alpine bird

Abstract: To track peaks in resource abundance, temperate-zone animals use predictive environmental cues to rear their offspring when conditions are most favourable. However, climate change threatens the reliability of such cues when an animal and its resource respond differently to a changing environment. This is especially problematic in alpine environments, where climate warming exceeds the Holarctic trend and may thus lead to rapid asynchrony between peaks in resource abundance and periods of increased resource requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
6
16
0
Order By: Relevance
“…Later arrival can reduce fecundity since late broods usually have lower survival (Kokko 1999, Lerche‐Jørgensen et al 2018), and the short season reduces the chance for successful second broods or replacement broods (Buchmann 2001, Morrison et al 2019, but see Low et al 2015). In addition, in arctic and mountain habitats, strong extreme weather events are more frequent compared to low‐land habitats (Schmidt et al 2019, Schano et al 2021). This could hamper the bird's ability to predict favourable breeding conditions and challenges the possibility to adapt their annual cycle to local habitat (McNamara et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later arrival can reduce fecundity since late broods usually have lower survival (Kokko 1999, Lerche‐Jørgensen et al 2018), and the short season reduces the chance for successful second broods or replacement broods (Buchmann 2001, Morrison et al 2019, but see Low et al 2015). In addition, in arctic and mountain habitats, strong extreme weather events are more frequent compared to low‐land habitats (Schmidt et al 2019, Schano et al 2021). This could hamper the bird's ability to predict favourable breeding conditions and challenges the possibility to adapt their annual cycle to local habitat (McNamara et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This could hamper the bird's ability to predict favourable breeding conditions and challenges the possibility to adapt their annual cycle to local habitat (McNamara et al 2011). As a result, the phenology of alpine populations could be subject to more inter‐individual variation (Schano et al 2021). In this study, the phenology in spring is more different between individuals of the German low‐land population, although samples size might have been too small for reliable detection.…”
Section: Discussionmentioning
confidence: 99%
“…There is striking evidence that white‐winged snowfinches are strictly associated with cold alpine environments, in terms of their distribution (Brambilla et al 2017a, 2020, Brambilla and Delgado 2020, BirdLife International 2021, de Gabriel Hernando et al 2021), foraging areas (Antor et al 1995, Brambilla et al 2017b, 2018), social behaviour (Delgado et al 2021), survival rates (Strinella et al 2020) and habitat and nest‐site selection (Heiniger 1991a, b1991b, Brambilla et al 2017b, Bettega et al 2020, Niffenegger 2021). The dependence of this species on cold environments is particularly strong during the breeding season (Brambilla et al 2019, 2017a, Resano‐Mayor et al 2019, Schano et al 2021, Alessandrini et al 2022, de Gabriel Hernando et al 2022): the breeding distribution of the species in European mountains is associated with low values of annual average temperature (Brambilla et al 2017a, 2020, 2017a, de Gabriel Hernando et al 2021), suggesting a thermal niche much narrower than that suggested by Cobos et al (2021). Similarly, during winter the species appears almost invariably tied to mountain sites above the treeline (Heiniger 1991a, Bettega et al 2020, Resano‐Mayor et al 2020, Delgado et al 2021, de Gabriel Hernando et al 2021; see also the wintering distribution according to BirdLife International 2021), with season‐specific distribution models showing how suitable areas during the cold season extend only partly to lower mountain ranges (de Gabriel Hernando et al 2021).…”
Section: A Worked Example: the Thermal Niche Of The White‐winged Snow...mentioning
confidence: 99%
“…Often overlooked in this discussion, however, is the impact of glacier loss on the biodiversity living on and adjacent to glaciers (Hardy et al . 2018; Schano et al . 2021; Stibal et al .…”
Section: Introductionmentioning
confidence: 99%
“…Well-known impacts of glacier recession include the loss of key meltwater resources which transport nutrients to downstream habitats (Ren et al 2019), underpin communities (Giersch et al 2017. Often overlooked in this discussion, however, is the impact of glacier loss on the biodiversity living on and adjacent to glaciers Schano et al 2021;Stibal et al 2020).…”
Section: Introductionmentioning
confidence: 99%